Diagnostic value of a spiral breast computed tomography system equipped with photon counting detector technology in patients with implants: An observational study of our initial experiences. Issue 30 (24th July 2020) - Ruby, Lisa; Shim, Sojin; Berger, Nicole; Marcon, Magda; Frauenfelder, Thomas; Boss, Andreas
Abstract : Abstract: To evaluate the value of a breast computed tomography (CT) (B-CT) in assessing breast density, pathologies and implant integrity in women with breast implants. This retrospective study was approved by the local ethics committee. B-CT images of 21 women with implants (silicone/saline; 20 bilateral, 1 unilateral) who underwent opportunistic screening or diagnostic bilateral B-CT were included. Breast density, implant integrity, extensive capsular fibrosis, soft tissue lesions and micro-/macrocalcifications were rated. In 18 of the 21 women, an additional ultrasound and in two patients breast magnetic resonance imaging was available for comparison. The average dose was calculated for each breast using verified Monte Carlo simulations on 3D image data sets. Breast density was nearly completely fatty (ACR a) in two patients, scattered fibroglandular (ACR b) in five, heterogeneously dense (ACR c) in ten and very dense (ACR d) in four women. In three women showed a unilateral positive Linguine sign indicative of an inner capsule rupture. Extensive capsular fibrosis was found in three women. In three women, soft tissue lesions were depicted, which revealed to be cysts (n = 2) and lymph nodes (n = 1) on subsequent sonography. Diffuse, non-clustered microcalcifications were found in nine women. Eleven women showed cutaneous or intramammary macrocalcifications. Average dose was 6.45 mGy (range 5.81–7.28 mGy). In women with implants, B-CT presents a promising modality for evaluating breast density, implant integrity, extensive capsular fibrosis, soft tissue lesions and micro-/macrocalcifications without the need of breast compression utilizing a lower dose compared to doses reported for conventional four-view mammography.